Purchasing Decisions Through the 4C ​​Marketing Mix (To Customers of The Gade Coffee & Gold Bogor) - Ibnu Muttaqin; Hirayanti Hutabarat (The Management Journal of Binaniaga, 2022)
This research purposes to determine the effect of the 4C marketing mix on the purchasing decisions of the customers of The Gade Coffee & Gold Bogor. This research uses a quantitative approach with research data collection through questionnaires. The population in this research were all customers of The Gade Coffee & Gold Bogor and the sample used was 150 respondents with accidental sampling technique. The results showed that partially customer value, cost to customer, convenience and communication had a positive and significant effect on purchasing decisions. Meanwhile, simultaneously, the 4C marketing mix has a positive and significant effect on purchasing decisions.